Pedestrian routes and accessibility to urban services: An urban rhythmic analysis on people's behaviour before and during the Covid-19 - Zecca, Cecilia; Gaglione, Federica; Laing, Richard; Gargiulo, Carmela (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The emergency of Covid-19 changed the face of our cities, preventing most of the urban activities, limiting travels on large, medium and short distances and drastically reducing the number and the intensity of social relationships. The restrictive measures, imposed to the entire population, sensibly affected the experience of our built environment as well as the assets of pedestrian and cycling network that lead to the achievement of essential urban services. On one hand these limitations drastically imposed a change in the people's habits who spend now more time walking and cycling in absence of any other entertainments; on the other, they have revealed the need of a reorganisation of pedestrians and cycling paths as well as of open spaces. The morphology of these urban spaces are unable to cope with the current social-distancing situation and to adapt to a “new different routine”. Local decision makers face with a new demand of urban space for pedestrian and cycling accessibility which have been so far unexplored. In order to contribute to future planning decisions, the document proposes a comparison between pedestrian flows and accessibility to urban services during the blockade, taking two districts in the city of Aberdeen as a case study. By adopting an urban rhythmic analysis, the selected areas were monitored on a weekly basis during different periods during the days in order to quantify the intensity of the user, the available services and their opening and closing times also change the date obtained from rhythmic analysis they are associated in a GIS environment in order to classify urban areas. Drawn on the concepts of new social distancing and switch of life/working habits as main factors for redesigning the pedestrian and cycling urban spaces, the paper proposes, as a conclusion, specific urban design recommendations in order to deal with emergency situations, such as an outbreak movement limitation.